IR Spectroscopic Studies on Water Confined in an Isoreticular MOF Series–Influence of the Metal and Linker Functionality - Tabea C. V. Haug; Frank Hoffmann; Merve N. Tasova; Roy Heffels; Michael Fröba (Advanced Materials Interfaces)
Abstract Mono‐ and bimetallic MOF‐74 samples with different ratios of Mg2+ and Ni2+ (9:1, 7:3, and 1:1), as well as Ni‐MOF‐74 analogs with different pore sizes and functionalities, were loaded with water through the exposure to a controlled relative humidity. To get information on the influence of the metal, pore size (1.2–3.6 nm), and functionality on the confined water, all samples were analyzed through infrared spectroscopy and the results were correlated to corresponding water sorption isotherms. Deconvolution of the O‐H stretching vibrational band made it possible to draw conclusions about differently ordered water species inside the pores. In all samples, it was visible that at lower pore loadings, the MOFs mostly comprised of less ordered water species, while higher pore loadings led to an increased formation of a more ordered, tetrahedral phase. Increasing amounts of Ni2+ within the series of bimetallic Mg/Ni‐MOF‐74 samples gave the hydrated systems a more hydrophilic behavior and favored the growth of more ordered species. Moreover, larger pores favored the less ordered water species, while hydrophilic functionalities led to the growth of water with a higher tetrahedrality and hydrophobic groups led to pores dominated by less ordered water species but can also have an ordering effect.